Masyarakat Lokal dalam Konfigurasi Kapitalisme Negara di Sektor Pariwisata Studi Kawasan Ekonomi Khusus Mandalika - Chaniago, Dwi Setiawan; Nugroho, Heru; Isbah, M Falikul (Jurnal Sosiologi Andalas, 2024)
Local communities face a situation of infiltration of state capitalism along with the development of the Mandalika Special Economic Zone in Central Lombok. The process of developing regional infrastructure and regional infrastructure carried out by the Development and Management Business Entity with the large support of State-Owned Enterprises raises the question of the extent to which the development process carried out has implications for the lives of local communities. This study aims to determine the implications of the state capitalism approach in the development of the Mandalika special economic zone for local communities as seen from the implementation of the MotoGP event in the Mandalika area. This research is a case study research with a qualitative approach. This research shows an imbalance in the role of state statism intervention in the distribution of benefits from economic regulatory activities by SOEs that are more business-oriented than social development in favor of local communities. This is because the strategy of infrastructure development and event implementation in the region operates in the realm of political goals rather than achieving economic goals at the local level. The support of state statism through events is politically directed to stimulate the activities of business actors in the region and attract investors to be further involved in regional development rather than oriented towards the benefits of local communities directly. The configuration of state capitalism actors in the operation of Mandalika SEZ shows the characteristics of state capitalism characterized by economic inclusive nationalism that combines state statism intervention through strengthening the role of BUMN while opening up opportunities for the involvement of international investors, corporations and business actors in supporting regional development.